Design Of A Marketing Information System To Improve The Competitiveness Of Sihobuk Peanut Umkm Using The Prototype Method (Case Study: Sipoholon Traditional Market) - Sthepy Situmeang; Supiyandi; Ahmad Akbar (Bahasa Indonesia, 2026)
The Sihobuk Peanuts MSME has great potential in business development, but still experiences obstacles in marketing activities that have not utilized information technology optimally, resulting in low competitiveness. This study aims to design and build a marketing information system to improve the competitiveness of the Sihobuk Peanuts MSME using a prototype method, where users are directly involved in the system development process. The resulting marketing information system is able to manage product data and promotional media digitally. The results of the study indicate that the system built can help expand marketing reach and increase promotional effectiveness, so it is expected to increase the competitiveness of the Sihobuk Peanuts MSME.